METODE PEMBELAJARAN DI LUAR KELAS (OUTDOOR STUDY), MELALUI MEDIA MUSEUM RUMAH STUDI MISI OSF SEMARANG LEARNING METHODS OUTSIDE THE CLASSROOM (OUTDOOR STUDY), THROUGH THE MEDIA MUSEUM OSF SEMARANG MISSION STUDY HOUSE - FR Wuriningsih (LPPM Universitas 17 Agustus 1945 Semarang, 2022)
Learning activities outside the classroom (Outdoor Study) and outside reading book texts will create a different atmosphere and understanding. One of the ways to study outdoors is to visit museums, the museum informs the public, especially students and teachers, about history classes. Museums are the best place to find historical sources, feel more grateful, get to know the world more broadly. The purpose of this community service writing is to disseminate information about the existence of the OSF Semarang Mission Study House as an alternative to visit, as an interesting place and provide additional knowledge. The methods used in this activity are preparation, visit and evaluation. The result of this dissemination is that the OSF Semarang Study house is an interesting place to visit with relics of interesting items to be known by students and the visiting public. Arrangement of items in a neat and attractive room will make students and the public feel at home and will visit again